Dolaylı vergiler ve kayıt dışı ekonomi - Kanlı, Murat (My University, 2007)
DOLAYLI VERGİLER VE KAYIT DIŞI EKONOMİ Kayıtdışı ekonomik faaliyetler, kamu finansmanını sağlamayı güçleştirdiği ve makro ekonomik göstergelerin sağlıklı olmasını engelledikleri için ekonomi politikalarının belirlenmesini ve uygulanan politikaların başarısını olumsuz etkilemektedirler. Dolaylı vergiler ise tahsilâtı kolay olduğu için vergi gelirlerini artırmanın yanında vergi adaletini bozucu etki yaratmaktadırlar. Özellikle 1980 sonrasında kayıt dışı ekonomi ve dolaylı vergiler sürekli bir artış göstermişlerdir. Bu çalışma da kayıt dışı ekonomi ile dolaylı vergilerin birbirlerine etkilerinin olup olmadığı, eğer böyle bir etkileşim söz konusu ise bunun nedenlerinin neler olduğu anlatılmaya çalışılmıştır. Kayıt dışı ekonominin artmasıyla birlikte gelir üzerinden alınan vergilerin hâsılatlarında azalma meydana gelmiştir. Kamunun gelir kısmında meydana gelen bu açığı kapatmak içinde dolaylı vergiler artırılmıştır. Dolaylı vergiler kişilerin gelirlerine göre değil de harcamalarına göre, herkesten aynı oranda alındığı için vergilemede adaleti bozucu ve bireyleri kayıt dışı ekonomiye sevk edici etkileri vardır.

INDIRECT TAXES AND UNDERGROUND ECONOMİCS Underground economic activities prevent to determine economics policies and affect the succeed of practising politics in a negative way. Because underground economic activities make the more difficult to finance ‘public financing’ and hinder the macro economics signs to be healty. As for indirect taxes can be collected easily. For this reason, these taxes increase taxes revenue. Despite of this advantage, indirect taxes create effects of the breaking off tax justice. Especially after 1980s underground economy and indirect taxes can be notice that a continous increase. This thesis is trying to explain that whether underground economic activities and indirect taxes are being affected each-other. On the other hand at this thesis show that if they are beıng affected each-other. Namely, if there is a connection at underground economic activities and indirect taxes what the reasons of this connection is discussing. Increase of underground economic activities take form decreasing products to taxable income. For covering the deficits at the revenues of public is weighted on using of the indirect taxes. Indirect taxes are being collected spenditure of individuals not the revenues. At this connection indirect taxes have effects of breaking off taxation justice because of not being collected the same ratio from everybody and besides have effects to inclined individuals towards to the underground economy.
Keywords: Kayıt Dışı Ekonomi; Maliye; Vergi Denetimi